The effect of good governance on business creation: a multilevel approach - María Jesús Rodríguez-Gulías; Vítor Manuel de Sousa Gabriel; David Rodeiro-Pazos (Revista de Economía Mundial, 2020)
Different studies had point out the importance of public governance to promote entrepreneurship. We used multilevel modelling on a sample of 206 countries, for the period 2004-2014, to empirically test three hypotheses. Firstly, whether business creation is determine by the regions. Secondly, the immediate impact of governance on entrepreneurial entry rates and thirdly, delayed effect of governance was considered. Our results showed countries located in the same region are more homogeneous in terms of entrepreneurship. Also, a significant immediate effect of Rule of Law and Regulatory Quality and a delayed effect of several variables were detected.